STUDY OF EYE HEALTH RISKS ASSOCIATED WITH DECORATIVE COSMETICS AND AESTHETIC PROCEDURES - T. Mihova; E. Georgieva; S. Trifonova-Laskova (Trakia Journal of Sciences, 2025)
INTRODUCTION: The cosmetic industry has seen significant growth, with an increasing number of men utilizing procedures and rejuvenation therapies. This shift has expanded the consumption of cosmetic services but also raised concerns about risks affecting eye health. Cosmetic products and procedures can cause irritation, allergies, and infections, posing serious health risks. AIMS: This study analyzes trends in the use of cosmetic products and facial procedures, aiming to assess their potential risks to eye health. METHODS: A documentary method was applied, involving a systematic review of literature from electronic databases such as PubMed, Scopus, Web of Science, and Research Gate using specialized software. The analysis focused on existing trends and risks related to cosmetic procedures, with keywords including "dry eye," "eye cosmetics," "safety," "cosmeticians," and "opticians." A sociological method was also employed through a survey conducted in November 2024 among students (n=53) and faculty members (n=5).RESULTS: Survey data indicated that 55.2% (n=32) of participants experienced burning or irritation in their eyes after procedures such as chemical peels and micropigmentation. More severe reactions, such as allergies or burns, were reported by 10.3% (n=6) of respondents. The findings highlight the need for educational campaigns to promote safe cosmetic practices. CONCLUSION: Improved health awareness among medical professionals and consumers about the risks of cosmetic procedures is essential. Educational campaigns targeting both consumers and professionals are recommended. Systematic information on the safety of these procedures is needed.